Mechanism of action of somatostatin in pancreatic β-cells: oxidative metabolism, glycolysis pathway and role of extracellular calcium influx - Alahmed, Jala Amir Salman (2019)
The mechanism of action of somatostatin (SRIF) has been extensively studied during the last five decades since the discovery of the peptide in 1974. However, there are many concealed actions of the peptide to control insulin secretion from pancreatic β–cells. This can contribute to resolving the dilemmas of cancer and diabetes mellitus. To achieve this goal, the MIN6 cell line was used as a model of insulin secreting pancreatic β-cells. Polarographic oxygen and enzymatic lactate electrodes were used to measure oxygen consumption rate (OCR) and lactate production rate, respectively. Imaging techniques were used to measure the mitochondrial membrane potential (ΔΨmit) using Rhodamine 123 (Rh123) dye and Ca2+ influx using Fluo-4 probe. Glucose uptake and ATP production were measured by Promega® plate-based assays, the Glucose Uptake-Glo™ Assay, and CellTiter-Glo® 2.0 Assay, respectively. 100 nM SRIF significantly and equally inhibited OCR stimulated by both 10 mM glucose and 10 mM α-ketoisocaproate (KIC); this effect was not seen in the absence of substrates. 10 mM glucose significantly decreased basal Rh123 fluorescence, the effect was reversed by 100 nM SRIF. In Ca2+ free condition, 100 nM SRIF did not affect ΔΨmit while it depolarized ΔΨmit in the presence of nifedipine. The peptide had no effect on ATP production either in the presence or in the absence of each mitochondrial fuels. It neither affected the glucose uptake nor the glucokinase activity in MIN6 cells. The peptide also inhibited lactate production in the absence and presence of 1 µM cyclosporine A (CSA) but not in the presence of each 100 nM okadaic acid (OKA) or ethanol. SRIF decreased the basal and substrate-induced Ca2+ influx into MIN6, the effect was abolished by pre-incubation of the cells with pertussis toxin (PTX). 1 µM dibutyryl cAMP significantly decreased the inhibitory action of SRIF.